Translating Education for Sustainable Development Into Economics Pedagogy: A Qualitative Study of Prospective Teacher Educators - Muhammad Khusen; Muhammad Feriady (Lembaga Teewan Journal Solutions, 2026)
Education for Sustainable Development (ESD) depends not only on teachers but also on the teacher educators who prepare them. However, prospective economics teacher educators remain underexplored in ESD research, particularly in developing-country contexts. This study examines how prospective economics teacher educators in Indonesia perceive ESD, envisage its integration into economics teaching, and identify barriers and support needs. Using a qualitative content analysis design, data were collected through an open-ended survey of 18 master’s students in Economics Education at Universitas Negeri Semarang and semi-structured interviews with five information-rich participants. Data were analysed in NVivo 15 using inductive coding, thematic categorisation, and frequency-based pattern analysis. Findings reveal three main patterns. First, participants’ understandings of ESD were transitional, combining integrative sustainability perspectives with residual environmental framings and uneven conceptual depth. Second, a perception–practice gap emerged in translating ESD into learning objectives, pedagogy, and assessment of attitudinal and behavioural change. Third, sustainability was often viewed as an addition to economics rather than intrinsic to economic reasoning, while limited conceptual understanding, teaching experience, materials, mentoring, and institutional support were identified as key barriers. The study highlights the need for structured preparation that strengthens pedagogical translation, assessment competence, and sustainability-oriented economic thinking.